Phytochemical Analysis and Antibacterial Activity of the Stem of Barleria cuspidata Using Different Solvent Extracts - S. M. Mehatar; K.V. Badar; M. S. Jamdhade (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The study aims to investigate the phytochemical constituents and antibacterial activity of the stem of Barleria cuspidata, an important medicinal plant. Various solvent extracts, including Aqueous extracts, ethanol, methanol, and Acetone extracts, were prepared to assess their phytochemical profiles and antibacterial properties. The phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and other bioactive compounds. The antibacterial activity was evaluated against common bacterial pathogens such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella typhimurium using the agar well diffusion method. The results indicated that the ethanol and methanol extracts exhibited significant antibacterial activity, suggesting that Barleria cuspidata stem possesses potential as a natural source of antibacterial agents.